The Impact of Slaughtering Female Cattle Compared to Males on the Sustainability of Livestock Production in Libya A Survey Study (Comprehensive Journal of Science, 2026)
This study was conducted at the Al-Ajilat Central Slaughterhouse. It was a cross-sectional study that included a questionnaire to identify the causes of meat wastage in female livestock and to determine the pregnancy rates of slaughtered female livestock in the study area. Additionally, the economic and meat/livestock losses resulting from animal wastage were estimated based on the current monetary values ​​of the average adult weight of female sheep and goats (approximately 30 kg), female cattle (approximately 250-300 kg), and female camels (approximately 150 kg). These values ​​were determined through a market survey (random sampling) conducted at the Al-Ajilat Central Slaughterhouse during October-November 2025. The survey addressed the causes of indiscriminate slaughter of female livestock, particularly pregnant animals, and provided a scientific perspective on animal welfare aspects related to the slaughter of female livestock. It also assessed the prevalence of slaughtering animals during a critical growth stage, when fetuses may be exposed to adverse effects. Given the limited data available on the prevalence of slaughter in Libya and the associated uncertainties, a systematic process of gathering knowledge from experts was deemed necessary. This process aimed to reduce the slaughter of female livestock, which leads to decreased future meat and milk production and the potential extinction of the local breed. Driven by high meat demand, ignorance of pregnancy status, and economic hardship, this practice can result in significant waste. Estimates suggest that the average percentage of animals slaughtered is (0.31, 50, 48.13, 40, 50, 60.13, 1, 34, 0, 70, 88, 1) for cattle, camels, sheep, and goats, respectively. This practice reduces the size of livestock herds nationally and harms Libya's agricultural economy.